PENGARUH RISIKO BISNIS, PERTUMBUHAN PENJUALAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL - Rindiasih, Riski; Wulandari, Rosita (Politeknik Negeri Ambon, 2023)
The key to maximizing the company's footprint is a well-thought-out financing structure. The capital structural will be the determining factor of a company's performance. The objective of this study is to run tests and collect data on the effect of business risk, sales growth, and asset structure on capital structure. This analysis focuses on Property and Real Estate companies listed on the IDX between 2017 and 2021. The purposive sampling method was used to determine the sample, so that a sample of 12 property and real estate companies was obtained in 2017-2021, obtaining a research sample of 60 data. The data processing technique was carried out using panel data multiple regression through the help of Eviews version 9. As a result of this study, capital structure is influenced by business risk, sales growth, and asset structure. business risk has an influence on capital structure whereas sales growth and asset structure have no influence on capital structure.